Evaluation of 3D deformation field in siltstone with a pre-existing 3D surface flaw under uniaxial compression using X-ray computed tomography and digital volumetric speckle photography. (15th February 2022) - Mao, Lingtao; Lei, Yu; Ding, Leilei; Wu, Jingcheng; Li, Liyun; Yang, Min; Ju, Yang; Chiang, Fu-pen
Highlights: Loading and in situ CT imaging are performed on siltstone with 3D surface flaws. Interior 3D deformation in specimens is quantified using DVSP methods. The propagation mechanism of the 3D surface flaw is characterized. Abstract: The interior deformation or rupture of materials is usually derived from measuring the surface deformation of specimens. In this study, a set of uniaxial compression tests combined with in situ X-ray computed tomography (CT) was performed on siltstone specimens with a pre- existing three-dimensional (3D) surface flaw with various inclination angles (α = 30 ◦, 45 ◦, 60 ◦ ). The ratio of flaw depth to specimen thickness was 0.26. Based on the CT images of the specimens under different loads, the digital volumetric speckle photography procedure was applied to quantifying the 3D interior deformation of the specimens, and 3D displacement and major principal strain ε1 distribution in different sections were determined. The characteristics of internal strain before specimen fracturing indicated strain localization, which could describe the propagation mechanism of the single 3D surface flaw.